2010
DOI: 10.1038/sj.bjc.6605605
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation for the treatment of epidermoid anal cancer: 13-year follow-up of the first randomised UKCCCR Anal Cancer Trial (ACT I)

Abstract: demonstrated the benefit of chemoradiation over radiotherapy (RT) alone for treating epidermoid anal cancer, and it became the standard treatment. Patients in this trial have now been followed up for a median of 13 years. METHODS: A total of 577 patients were randomised to receive RT alone or combined modality therapy using 5-fluorouracil and mitomycin C. All patients were scheduled to receive 45 Gy by external beam irradiation. Patients who responded to treatment were recommended to have boost RT, with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
215
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(248 citation statements)
references
References 17 publications
17
215
1
15
Order By: Relevance
“…Earlier phase iii trials have used a single bolus of mmc at 12-15 mg/m 2 or 2 cycles at 10 mg/m 2 . In our study, mmc was prescribed at a lower dose of 10 mg/m 2 , but survival outcomes in the two study arms were similar [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier phase iii trials have used a single bolus of mmc at 12-15 mg/m 2 or 2 cycles at 10 mg/m 2 . In our study, mmc was prescribed at a lower dose of 10 mg/m 2 , but survival outcomes in the two study arms were similar [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…The ccrt regimen in trials conducted by the U.K. Co-ordinating Committee on Cancer Research (act i) and the European Organisation for Research and Treatment of Cancer used a single cycle of mmc and, compared with rt alone, demonstrated superiority in locoregional control and disease-free survival (dfs). However, no overall survival (os) benefit was found [6][7][8] . The Radiation Therapy Oncology Group (rtog) 87-04 trial similarly demonstrated significant improvements in colostomy-free survival and dfs with the addition of 2 cycles of mmc to 5fu and rt, but again, no survival benefit was observed 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ses résultats ont été récemment publiés [2]. Elle confirme la supériorité de la RCT sur la RT exclusive en termes de réduction du risque de récidive locorégionale (HR = 0,46 ; IC 95 % : 0,35-0,60 ; p < 0,001 ; réduction absolue de 25,3 % à 12 ans entre les 2 groupes) et d'amélioration de la survie sans récidive (HR = 0,70 ; IC 95 % : 0,58-0,84 ; p < 0,00 ; résolution absolue de 12 % à 12 ans entre les 2 groupes) et de la survie sans colostomie (HR = 0,76 ; IC 95 % : 0,63-0,91 ; p < 0,001 ; réduction absolue de 9,5 % à 12 ans entre les 2 groupes).…”
unclassified
“…Treatment regimens for SCC of the anal canal have evolved over the past decades, and studies have included comparisons of radiotherapy alone versus chemoradiation [7][8][9]; determining treatment benefits of mitomycin C (MMC) [10,11]; and comparisons of MMC with cisplatin [6,[12][13][14][15]. The accepted current standard regimen for patients with stage I-III SCC of the anal canal is radiotherapy (50.4 Gy) with concurrent infusional 5-fluorouracil (5-FU) administered days one through four during weeks one and five and MMC administered on day one of week one.…”
Section: Introductionmentioning
confidence: 99%